Healthcare costs in patients with metastatic lung cancer receiving chemotherapy - Vera-Llonch Montserrat; Weycker Derek; Glass Andrew; Gao Sue; Borker Rohit; Barber Beth; Oster Gerry (BMC, 2011)
Abstract Background To characterize healthcare resource utilization and costs in patients with metastatic lung cancer receiving chemotherapy in the US. Methods Using data from a large private multi-payer health insurance claims database (2000-2006), we identified all patients beginning chemotherapy for metastatic lung cancer. Healthcare resource use (inpatient, outpatient, medications) and costs were tallied over time from date of therapy initiation ("index date") to date of disenrollment from the health plan (in most instances, presumably due to death) or the end of the study period, whichever occurred first. Healthcare utilization and costs were characterized using Kaplan-Meier sample average methods. Results The study population consisted of 4068 patients; mean (SD) age was 65 (11) years. Over a median follow-up of 334 days, study subjects averaged 1.5 hospital admissions, 8.9 total inpatient days, and 69 physician office and hospital outpatient visits. Mean (95% CI) cumulative total healthcare costs were $125,849 ($120,228, $131,231). Costs of outpatient medical services and inpatient care constituted 34% and 20% of total healthcare costs, respectively; corresponding estimates for outpatient chemotherapy and other medication were 22% and 24%. Conclusion Our study sheds additional light on the burden of metastatic lung cancer among patients receiving chemotherapy, in terms of total cost thru end of life as well as component costs by setting and type of service, and may be useful in informing medical resource allocation in this patient population.